Clinical Manifestation, Diagnosis, and Surgical Treatment of Chronic Radiation Ulcers Related to Percutaneous Coronary Intervention. (March 2016) - Lee, Biing Luen; Ma, Hsu; Perng, Chern Kang; Wang, Tien Hsiang; Liao, Wen Chieh; Yeh, Fa Lai; Shih, Yu-Chung
Abstract : Abstract: Chronic radiation ulcers that develop after cardiac catheterization have become common recently because of the rapid increase in the use of diagnostic and interventional cardiac catheterization procedures. However, their diagnosis and treatment remain difficult. We encountered 10 patients with National Cancer Institute grade 4 radiation ulcers related to prolonged percutaneous coronary intervention. Data of these 10 patients, including clinical presentations and treatments, were collected and analyzed. A quality-of-life questionnaire was administered to the patients preoperatively and postoperatively. Most of the lesions (8/10 patients) were located on the back. All of the patients received prolonged cardiac catheterization lasting for more than 3 hours, at least once, and all of the coronary artery lesions showed chronic total or near-total occlusion. The surgical procedures included complete resection of the lesion followed by fasciocutaneous flap coverage (9/10) or skin grafting (1/10). The mean ± SD follow-up time was 23.3 ± 19.79 months, and the wounds in all the patients healed well without complications. After the surgery, the symptoms reduced and the quality of life improved significantly according to the scores in the quality-of-life questionnaire. In conclusion, the early diagnosis of chronic ulcers related to prolonged percutaneous coronary intervention depends on careful history taking and a highly suspicious clinical presentation. For National Cancer Institute grade 4 radiation ulcers, complete resection and immediate reconstruction with flaps or grafts may improve the symptoms and achieve reliable wound coverage without complications.